A New Measure of Stereotypes in the Workplace - Stanislava Bajziková; Lubomír Cing (Prague University of Economics and Business, Faculty of International Relations (FIR), 2020)
We introduce a new measure of stereotypes based on the principle of a multiple-price list: the elicitation of willingness to have an ethnic minority member in a team. We apply it on an example of the Roma in the Czech Republic and test on a sample of 100 students from the majority population. We also estimate the role of statistical discrimination, taste-based discrimination, and the contact hypothesis. Our results show small but significant mistreatment of the Roma. The choice to (not) have a Roma in a team seems to be driven by tastes, while the role of statistical discrimination and the contact hypothesis is rather limited.
Keywords: C91; Z13; 330; Stereotypes; Roma; discrimination; experiment